1997
DOI: 10.1016/s0029-7844(97)00117-8
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma arising from mature cystic teratoma of the ovary: A clinicopathologic analysis

Abstract: This study suggests that pathologic factors, grade, and mode of infiltration can provide valuable information for predicting the survival of patients with squamous cell carcinoma arising from mature cystic teratoma. In addition, squamous cell carcinoma antigen may be a useful marker to detect this disease preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
0
6

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 12 publications
7
80
0
6
Order By: Relevance
“…Ek olarak malign transformasyon riskini öngörebilecek henüz net bir bulgu veya yöntem mevcut değildir (3,4). Ancak literatürde tümör çapının 9.9 cm'den büyük olmasının %86 oranında malignite açısından sensitif olduğu bildirilmiştir (6 …”
Section: Discussionunclassified
“…Ek olarak malign transformasyon riskini öngörebilecek henüz net bir bulgu veya yöntem mevcut değildir (3,4). Ancak literatürde tümör çapının 9.9 cm'den büyük olmasının %86 oranında malignite açısından sensitif olduğu bildirilmiştir (6 …”
Section: Discussionunclassified
“…Gastrointestinal symptoms, rectal bleeding, or urinary frequency are various symptoms described and related to MCTs and they are attributed to invasion of nearby organs (4). The mean size of MCTs is 6-9 cm compared to malignant transformed MCTs which tend to have a larger size with an average mean size of 15cm (15,16). Kikkawa et al reported that a tumor size greater than 9.9 cm has a 86% sensitivity for malignancy (13).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases it is not diagnosed preoperatively (16,18,19). The use of tumor markers as a diagnostic tool to discriminate MCTs and SCCs arising from an MCT is difficult to help since most of them are raised in both situations (2).…”
mentioning
confidence: 99%
“…Larger size (>9.9cm) correlates with increased risk of malignant transformation. Prognostic indicators include FIGO staging, tumor rupture, vascular invasion and histological type of tumor 9 . Serum tumor markers (SCC-Ag &CEA) are mandatory for all such lesions.. Malignant tumors arising in a mature cystic teratoma spread by direct & local invasion rather than by lymphatic & hematogenous dissemination.…”
Section: Case Reportmentioning
confidence: 99%